Variation in laying date in relation to spring temperature in three species of tits (Paridae) and pied flycatchers Ficedula hypoleuca in southernmost Sweden. (10th February 2017) - Källander, Hans; Hasselquist, Dennis; Hedenström, Anders; Nord, Andreas; Smith, Henrik G.; Nilsson, Jan‐Åke
Abstract : This study documents the advancement of laying dates in three species of tits (Paridae) in southernmost Sweden during recent decades, and the absence of a similar response in the pied flycatcher Ficedula hypoleuca . It is based on several different nestbox studies; the oldest one starting in 1969. During 1969 to 2012, mean spring temperatures in the study area increased by between 0.06 and 0.08°C per year, depending on the period considered. Great tits Parus major, blue tits Cyanistes caeruleus and marsh tits Poecile palustris, which generally start egg laying between the last week of April and the first week of May, all advanced laying date at a similar rate during the study period (0.25 d yr –1 ). This indicates that these species were similarly affected by increasing temperatures. When accounting for mean spring temperature variation, we still found an advancement of laying date over the study period, mostly due to such relationships among marsh and blue tits. This result could reflect ongoing microevolution favouring earlier laying, but could also be a result of other factors such as increased intra‐ or inter‐specific competition for early breeding. Pied flycatchers, which generally lay during the third week of May, did not significantly advance the date of egg laying despite that the long‐term trend in the increase in ambient temperature during the 30‐d period preceding the start of egg laying was similar for pied flycatchers compared to the tit species.